Photothermally responsive icariin and carbon nanofiber modified hydrogels for the treatment of periodontitis - Zheng, Xiangjiao; Dong, Zhiqiang; Liang, Zepeng; Liu, Yu; Yin, Xiaowei; Han, Mofei; Cui, Zhongcheng; Mei, Xifan; Gao, Xiuqiu (Frontiers in Bioengineering and Biotechnology, 2023)
Periodontitis is a chronic inflammatory disease brought on by various bacteria, and effective antibacterial, anti-inflammatory and alveolar bone regeneration are the main goals of treating periodontal disease. In the current work, we employed Icariin (ICA) into a hydrogel modified with carbon nanofiber (CNF) to create a multifunctional composite nanoplatform. The composite was activated in the near infrared (NIR) to combine antibacterial, anti-inflammatory, and osteogenic activities to treat periodontitis. The antibacterial results showed that the ICA+CNF@H showed 94.2% and 91.7% clearance of S.aureus and E.coli, respectively, under NIR irradiation. In vitro experiments showed that NIR-irradiated composites suppressed inflammatory factor (IL-6) and ROS expression and up-regulated the performance of anti-inflammatory factor (IL-10) in RAW264.7 cells. At the same time, the composites promoted the production of osteogenic factors in BMSCs, with an approximately 3-fold increase in alkaline phosphatase activity after 7 days and an approximately 2-fold increase in the rate of extracellular matrix mineralization after 21 days. In vivo tests showed that the alveolar bone height was clearly greater in the ICA+CNF@H (NIR) group compared to the periodontitis group. In conclusion, ICA+CNF@H under NIR irradiation achieved a synergistic effect of antibacterial, anti-inflammatory, reduction of reactive oxygen species and promotion of osteogenesis, offering a novel approach for treating periodontitis.